2019
DOI: 10.1186/s12889-019-7371-3
|View full text |Cite
|
Sign up to set email alerts
|

Men’s participation in maternal and child health care in Western Uganda: perspectives from the community

Abstract: Background Participation of men in Maternal and Child Health (MCH) is crucial for the reduction of infant and maternal mortality. Men may be influential in making health care decisions that may affect their female partner’s access to health care services, but also as individuals, whose health status has a significant impact on the health of their partners’ and that of their children. However, male involvement is still inadequate due to various reasons. This paper sought to explore the community pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
6
34
2
Order By: Relevance
“…Although men are not direct beneficiaries of pregnancy related care services, their understanding, participation and support are crucial in order for women to access basic pregnancy related care services. Although many other factors contribute to increased maternal and infant morbidity and mortality in the developing countries, low male involvement is a major determinant and their participation has been shown to be vital for their reduction [19,21,22,41]. Despite the average involvement of men in pregnancy related care in this study, their involvement in performing care tasks such as accompanying their partner for antenatal and postnatal care; assisting in changing diaper of the baby was poor.…”
Section: Discussionmentioning
confidence: 54%
“…Although men are not direct beneficiaries of pregnancy related care services, their understanding, participation and support are crucial in order for women to access basic pregnancy related care services. Although many other factors contribute to increased maternal and infant morbidity and mortality in the developing countries, low male involvement is a major determinant and their participation has been shown to be vital for their reduction [19,21,22,41]. Despite the average involvement of men in pregnancy related care in this study, their involvement in performing care tasks such as accompanying their partner for antenatal and postnatal care; assisting in changing diaper of the baby was poor.…”
Section: Discussionmentioning
confidence: 54%
“…We found that gender, and sociocultural roles and norms within the home play an important role in care seeking for child illnesses in Kogi and Ebonyi states, Nigeria. Our findings add to a growing body of evidence that suggests that public health programs that exclusively target mothers of young children risk failure when they do not take into account the complexity of intrahousehold dynamics [8,19,30,31]. Seeking permission from a male partner can be a delay in seeking timely care for sick children.…”
Section: Discussionmentioning
confidence: 76%
“…We found that gender, and sociocultural roles and norms within the home play an important role in care seeking for child illnesses in Kogi and Ebonyi states, Nigeria. Our findings add to a growing body of evidence that suggests that public health programs that exclusively target mothers of young children risk failure when they do not take into account the complexity of intra-household dynamics (8,19,30,31). Seeking permission from a male partner can be a delay in seeking timely care for sick children.…”
Section: Barriers To Seeking Care For Sick Children Outside the Homementioning
confidence: 75%